2013
DOI: 10.2147/ppa.s43305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an animated diagram and video-based online breathing program for dyspnea in patients with stable COPD

Abstract: BackgroundBreathing programs have been reported to have positive effects in alleviating symptoms and optimizing pulmonary function in patients with chronic obstructive pulmonary disease (COPD). However, patients with stable disease may drop out of such programs if they are not modified to the individual’s exercise tolerance level, or if they are not easy to perform in the home. Little is known about the effectiveness of web-based home breathing programs for dyspnea. The purpose of this study was to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 26 publications
(21 reference statements)
0
39
1
Order By: Relevance
“…Our systematic review found that three studies in the category of interventions performed at home showed significant effects on the SGRQ subscores and total score in favour of the experimental group compared with controls (Akinci & Olgun, 2011;Ingadottir & Jonsdottir;Liu et al, 2013). In contrast to our findings, some studies included in an integrated review of home-based respiratory care showed a significant difference in favour of the experimental groups for activity and impact scores on the SGRQ, but no significant differences between groups for the symptom score or total score (Jonsdottir, 2008).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our systematic review found that three studies in the category of interventions performed at home showed significant effects on the SGRQ subscores and total score in favour of the experimental group compared with controls (Akinci & Olgun, 2011;Ingadottir & Jonsdottir;Liu et al, 2013). In contrast to our findings, some studies included in an integrated review of home-based respiratory care showed a significant difference in favour of the experimental groups for activity and impact scores on the SGRQ, but no significant differences between groups for the symptom score or total score (Jonsdottir, 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…In this category, one RCT was identified (Liu et al., ) and two studies with a two‐group pre–post design (Akinci & Olgun, ; Moriyama et al., ). These three studies used the SGRQ and included an online video‐based breathing programme (Liu et al., ), education about COPD and performance of breathing exercises and physical training (Akinci & Olgun, ), or a nurse‐led self‐management educational programme that included an interactive workbook, learning materials and journal for self‐monitoring (Moriyama et al., ). One study reported a positive effect in favour of the experimental group (MD = 15.6–18.2, p < 0.05) for all of the SGRQ scores (Liu et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of chronic disease, alternative treatments have often been sought to provide improved clinical features of COPD, emphasizing a better health-related quality of life. Liu et al 33 during a 4-month HBPR program, based on an online intervention, found a significant improvement in exercise tolerance, pulmonary function, and the health-related quality of life reported by patients with stable COPD. To this end, different questionnaires on the quality of life remain important assessment tools.…”
Section: Discussionmentioning
confidence: 99%
“… 4 However, for those unable or unwilling to attend group classes, IT-based approaches can provide support. 6 11 IT-based self-management and lifestyle-change interventions for COPD have reported improved health-related quality of life, 9 , 12 16 physical activity, 13 , 14 , 17 exercise capacity, 12 , 16 and functional capacity 18 , 19 and reduced number and duration of hospital admissions. 9 , 18 , 20 23 Participants have shown improved knowledge and awareness of their symptoms and health status, 19 , 24 and qualitative analyses indicate positive effects on self-management, psychological condition, and coping ability.…”
Section: Introductionmentioning
confidence: 99%